Prinsip dan Nilai-Nilai Pendidikan Anti Korupsi dalam Qs. Al Baqarah: 188 - Umayyatun, Umayyatun (CV. Creative Tugu Pena, 2023)
This Improving noble morals is the main goal of Islamic education. A decrease in despicable morals, such as corrupt behavior, is an indicator of an increase in noble morals. Internalizing contextually oriented anti-corruption values by developing educational values in the Qur’an is the best strategy in fighting corruption. This research seeks to explore the values of anti-corruption education in the Qur’an, Surah al-Baqarah: 188. This is important to do in order to find a form that can give birth to new principles and values as well as paradigms in the mapping of Islamic science. Efforts to reconstruct the epistemology of the Qur’an. Strong and applied regulations are urgently needed to eradicate and prevent cases of corruption that have taken root in Indonesia. In this research, the method used is a qualitative approach which was chosen because it is closely related to the ideal values regarding anti-corruption education implicit in the Qur’an. This research uses a type of library study as the main approach. The primary data source used comes from tafsir books that are relevant to the research topic, while secondary data is obtained from various sources, including books, journals or articles, and other information. Data collection techniques are carried out through reviewing written documents. Meanwhile, for data analysis, the methods used are descriptive-philosophical methods, content analysis methods and thinking methods: inductive and deductive. Keywords: Improving Moral, Anti-Corruption Education, Anti-Corruption Education Values